1999
DOI: 10.1074/jbc.274.31.21707
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomes Bind to Cell Surface Proteoglycans

Abstract: Material on the surface of activated T-cells was displaced following incubation with a sulfated polysaccharide, dextrin 2-sulfate (D2S), and purified by anion-exchange chromatography. This revealed a complex comprising histones H2A, H2B, H3, and H4 and DNA fragmented into 180-base pair units characteristic of mono-, di-, tri, and polynucleosomes, a pattern of fragmentation similar to that found in apoptotic cells. An antibody raised against the purified nucleosome preparation bound to the plasma membrane of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 42 publications
2
59
0
2
Order By: Relevance
“…Furthermore, the results of the in vitro functional tests (e.g., neurite outgrowth from cerebellar neurons, Schwann cell process formation and proliferation, as well as migration of neural progenitor cells) indicated that extracellular histone H1 interacts with PSA at the cell surface and that this interaction induces the observed effects of histone H1 on the investigated neural cells. Indications for the unusual extracellular location of histone H1, which was first identified as a nuclear protein, have been found in several other studies: histone H1 has been observed at the cell surface of cultured mouse cortical neurons (Bolton and Perry, 1997), human monocytes (Holers and Kotzin, 1985), activated human peripheral blood lymphocytes (Watson et al, 1995), cultured T-cells (Watson et al, 1995(Watson et al, , 1999, a macrophage cell line (Brix et al,1998), and skeletal muscle cells (Henriquez et al, 2002). So far, the mechanism(s) by which histone H1 crosses the membrane are not known.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the results of the in vitro functional tests (e.g., neurite outgrowth from cerebellar neurons, Schwann cell process formation and proliferation, as well as migration of neural progenitor cells) indicated that extracellular histone H1 interacts with PSA at the cell surface and that this interaction induces the observed effects of histone H1 on the investigated neural cells. Indications for the unusual extracellular location of histone H1, which was first identified as a nuclear protein, have been found in several other studies: histone H1 has been observed at the cell surface of cultured mouse cortical neurons (Bolton and Perry, 1997), human monocytes (Holers and Kotzin, 1985), activated human peripheral blood lymphocytes (Watson et al, 1995), cultured T-cells (Watson et al, 1995(Watson et al, , 1999, a macrophage cell line (Brix et al,1998), and skeletal muscle cells (Henriquez et al, 2002). So far, the mechanism(s) by which histone H1 crosses the membrane are not known.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, heparan sulfates may inhibit HAT by binding directly to the enzyme. Alternatively, it is known that heparan sulfate can bind directly to histone proteins, and it has been speculated that heparan sulfate-histone interactions interfere with HAT-mediated acetylation of histone tails (40,41). Importantly, there does appear to be specificity in heparan sulfate inhibition of HAT because inhibition is dependent on the pattern of sulfation and on the length of the heparan sulfate chain (15).…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion of platelets and RBCs to NETs may be helped by electrostatic interaction of the negatively charged cells with positively charged histones in NETs (37). RBC adhesion to NETs could also play a role in sickle-cell disease, where a lethal crisis is often precipitated by infection (38).…”
Section: Discussionmentioning
confidence: 99%